Abordaje diagnostico, manejo y complicaciones de la hemorragia subaracnoidea - Encalada Aguilar, Christopher David (Machala : Universidad Técnica de Machala, 2024)
Subarachnoid hemorrhage (SAH) is a serious medical emergency characterized by the presence of blood in the subarachnoid space of the brain, usually due to a ruptured aneurysm. Sudden, intense headache, often described as "the worst headache of my life," is the most important and distinctive sign of this condition, often accompanied by nausea, vomiting, and neck stiffness. The global incidence of SAH is approximately 9 per 100,000 inhabitants per year, with a higher prevalence in women over 55 years of age. Significant risk factors include hypertension, smoking and genetic predisposition. Early diagnosis is based on computed tomography (CT) of the head, which confirms the presence of blood in the subarachnoid space. Treatment of SAH includes surgical interventions, such as aneurysm clipping, and endovascular procedures such as embolization, both aimed at preventing rebleeding, which is a leading cause of early mortality. Management of complications, such as vasospasm and hydrocephalus, is crucial to improve prognosis. Hospital mortality remains high, around 26%, and approximately 50% of survivors suffer some degree of significant morbidity. Despite advances in diagnostic and therapeutic techniques, SAH is still associated with a high mortality and morbidity rate. Continuing medical education and adherence to clinical guidelines are essential to optimize the management of this critical condition.
La hemorragia subaracnoidea (HSA) es una emergencia médica grave caracterizada por la presencia de sangre en el espacio subaracnoideo del cerebro, generalmente debido a la ruptura de un aneurisma. La cefalea intensa y súbita, descrita frecuentemente como "la peor cefalea de mi vida", es el signo más importante y distintivo de esta condición, a menudo acompañada de náuseas, vómitos y rigidez de nuca. La incidencia global de HSA es aproximadamente de 9 por cada 100,000 habitantes al año, con una mayor prevalencia en mujeres mayores de 55 años. Factores de riesgo significativos incluyen la hipertensión, el tabaquismo y la predisposición genética. El diagnóstico precoz se basa en la tomografía computarizada (TC) de cráneo, que confirma la presencia de sangre en el espacio subaracnoideo. El tratamiento de la HSA incluye intervenciones quirúrgicas, como el clipaje del aneurisma, y procedimientos endovasculares como la embolización, ambos dirigidos a prevenir el resangrado, que es una causa principal de mortalidad temprana. La gestión de complicaciones, como el vasoespasmo y la hidrocefalia, es crucial para mejorar el pronóstico. La mortalidad hospitalaria sigue siendo alta, alrededor del 26%, y aproximadamente el 50% de los sobrevivientes sufren algún grado de morbilidad significativa. A pesar de los avances en las técnicas diagnósticas y terapéuticas, la HSA sigue asociada a una elevada tasa de mortalidad y morbilidad. La educación médica continua y la adherencia a las guías clínicas son fundamentales para optimizar el manejo de esta condición crítica.
Keywords: HEMORRAGIA; HEMORRAGIA; SUBARACNOIDEA; CEFALEA